1995
DOI: 10.1002/cyto.990200405
|View full text |Cite
|
Sign up to set email alerts
|

High affinity binding of 7‐aminoactinomycin D and 4′,6‐diamidino‐2‐phenylindole to human neutrophilic granulocytes and lymphocytes

Abstract: The binding behavior of the DNA binding dyes 7-aminoactinomycin D (7-AAMD) and 4',6-diamidino-2-phenylindole (DAPI) to human neutrophilic granulocytes and lymphocytes was studied by image cytofluorometry. Peripheral blood leukocytes were prefixed in paraformaldehyde (PFA) and attached to cover glasses. Different fkation, permeabilization, and acid extraction methods were applied before the cells were stained to equilibrium using varying concentrations of 7-AAMD or DAPI. The apparent association constant and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…A decrease in fluorescence intensity can be explained by a decrease in the number of 7-AAMD binding sites or a reduced affinity. However, previous results have shown that the affinity constant was not affected by cell preparations unless nuclear proteins were removed (9). Therefore, the decrease in fluorescence intensity after PFA fixation is most probably an effect of a decrease in the number of available dye binding sites.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…A decrease in fluorescence intensity can be explained by a decrease in the number of 7-AAMD binding sites or a reduced affinity. However, previous results have shown that the affinity constant was not affected by cell preparations unless nuclear proteins were removed (9). Therefore, the decrease in fluorescence intensity after PFA fixation is most probably an effect of a decrease in the number of available dye binding sites.…”
Section: Resultsmentioning
confidence: 88%
“…7-AAMD accessibility to cultured fibroblasts has been shown to decrease with about 50% after PFA fixation (14), and we have also shown the importance of distinguishing between specific, high affinity binding, and non-specific dye binding (9). In this study we have used 7-AAMD to investigate the dynamics of PFA crosslinking of nuclear proteins to DNA.…”
mentioning
confidence: 94%
“…Human granulocytes were isolated from whole blood obtained from healthy donors and prepared as described previously (27).…”
Section: Materials and Methods Cellsmentioning
confidence: 99%
“…Many DNA binding fluorochromes show restrictions in their binding to DNA by the chromatin structure, and extraction of basic proteins results in an increased nuclear fluorescence intensity (11,12,15,19,21). Salt extraction of H1 also results in higher fluorescence intensity (15,23).…”
mentioning
confidence: 99%
“…An obvious candidate for the study of protein-DNA interactions is the DNA binding fluorochrome 7-aminoactinomycin D (7-AAMD), which is regarded as rather sensitive to such interactions (12,21,24). Actinomycin D may have some preference for active chromatin (3,34), where the amount of linker histones may be reduced.…”
mentioning
confidence: 99%